Absence of Asymptomatic Malaria Reservoirs in an Area with a Previous History of Local Malaria Transmission: A Successful Experience in Line with the Malaria Elimination Program in Iran - Zainab Hosseini; Kourosh Azizi; Mohsen Moghadami; Mehdi Hassaniazad; Reza Shafiei; Habibollah Turki (Tehran University of Medical Sciences, 2023)
Background: Asymptomatic malaria is a major challenge to be addressed in the implementation of the malaria elimination program. The main goal of the malaria surveillance system in the elimination phase is to identify reliably all the positive cases of malaria reliably (symptomatic and asymptomatic) in the shortest possible time. This study focused on the monitoring of asymptomatic malaria reservoirs in areas where local transmission had been previously established. Methods: It was a case-study approach that was conducted in the Anarestan area. A total of 246 residents and immigrants living in the area at the age range of 4-60 years old were randomly selected to be tested for malaria by microscope, RDT, and nested-PCR techniques. The inclusion criterion for participants to be entered into the study was the absence of specific symptoms of malaria. Moreover, participants who have been taking antimalarials for the last month were excluded from the study. Results: The results indicated no positive cases of asymptomatic malaria among the participants tested by all methods. Conclusion: The results of this study have shown that, without concerns for asymptomatic parasitic patients, a malaria elimination program has been successfully implemented within the studies area. In addition, the findings emphasized the existence of a strong malaria surveillance system in this area.